Polyarteritis nodosa in a 6-year-old girl – a case report and overview of current management techniques of the disease in paediatric patients - Nataša Marčun Varda; Mirjam Močnik (Acta Medico-Biotechnica, 2021)
Purpose: In this article a rare case report of a 6-year-old girl with polyarteritis nodosa (PAN) is presented and current clinical and treatment recommendations and new research data are reviewed. The latter is needed to clearly describe disease presentation, treatment responses, and prognosis in children. PAN is a rare form of vasculitis in children, affecting medium- and smallsized arteries. Its clinical presentation can be quite unspecific and insidious at the beginning, presenting a diagnostic problem.Methods: Presentation of the patient clinical characteristics, results of the investigation and treatment carried out, as well as the approach to management, treatment, and monitoring of patients with the same condition.Results: Patient diagnosis was confirmed by laboratory and morphological diagnostics. Treatment with corticosteroids and mycophenolate mofetil was introduced, which led to clinical improvement. The patient requires further lifelong follow-up. Conclusions: Early diagnosis and timely initiation of treatment are of the utmost importance for good prognosis and prevention of devastating irreversible impairment caused byPAN. New multicentre research is needed to improve the treatment of rare paediatric patients with this condition.